Judicial Pardon as an Alternative to a Judge's Decision - Ningtias, Ayu Dian; Nahdliyah, Hadziqotun; Shofa, Ahmad Faris (Jurnal Independent, 2025)
ABSTRACT There is a new concept in the renewal of criminal law, namely judicial pardon, this concept is also adopted by the Dutch legal system, in simple terms where the judge can forgive the defendant who is legally and convincingly proven to have committed a criminal offense. The formulation of the problem in this study is how the legal consequences of the enactment of the principle of judicial pardon in the Criminal Code 2023. From this research, the author analyzes that the legal consequences of the enactment of the principle of judicial pardon will largely have an impact on the character and nature of Indonesian criminal justice, and also has the potential to be one of the solutions to the current overcrowding problem. But the regulation of judicial pardon is still less specific, it also needs to be regulated in the Draft of the Criminal Procedure Code, such as in the form of a judicial pardon decision, there needs to be confirmation of the terms of judicial pardon, and it is also necessary to set limits or signs in order to obtain legal certainty and later not become a rubber article or become a multi-interpretation among judges.